Observations on the separate assessment of Prower-Stuart factor activities - Gardikas, C. (1962)
The activities of the Prower-Stuart factor in the first and second phase of thromboplastin production were separately assayed in 100 normal persons and 50 Dindevan-treated patients. It was found that in some of the subjects examined the two activities varied independently, and that some of the normal persons presented a partial deficiency of the factor. The implications of these findings are discussed.